Characterization of caprine embryonic stem cell-like outgrowths derived from the inner cell mass isolation - Abdullah, Ramli; Khadijah, W.E.W.; Goh, S.Y. (2012)
Embryonic stem (ES) cells have limitless potential in the field of biological sciences and regenerative medicine due to their pluripotency and ability for indefinite self-renewal. The aims of this study were: (i) to isolate goat ES cell lines from both in vivo and in vitro derived blastocysts and (ii) to characterize the growth characteristics and expression of markers indicative of pluripotency in goat ES cells. The goat inner cell mass (ICM) of in vitro and in vivo derived whole blastocysts was isolated by manually cutting or laser dissection, with in vitro cultured mouse embryonic fibroblasts (MEF's) as a feeder layer to obtain the ES cells. The in vivo derived blastocysts recorded a significant difference in producing goat ES cell lines at Passage 3, compared with in vitro derived blastocysts (91.7% vs. 20.8% respectively). The manually cut ICM (inner cell mass) isolation technique consistently recorded the highest success rate in goat ES cells for Passages 1 and 3, compared with the whole blastocyst culture (control) and those from the laser dissection technique (71.3% vs. 39.6% and 43.9%; 35.0% vs. 12.5% and 23.3% respectively). Alkaline phosphatase (AP), Oct-4 and SSEA-3 staining gave positive results in identifying the goat ES cells. In conclusion, goat ES cells could be produced by isolation of the ICM by using both manual and laser dissection of blastocysts, as characterized by AP, Oct-4 and SSEA-3 staining. Crown Copyright (C) 2012 Published by Elsevier B.V. All rights reserved.